Diálogo entre a tradição bíblica e a construção do discurso teológico ambiental cristão (Dialogue between bible’s tradition and the environment christian theological discourse construction) - Limeira, Amelia Ferreira Martins (Horizonte, 2012)
The biblical tradition has inspired environmental readings and interpretations by Christian theologians of various aspects, among which we highlight: Carriker, Reimer, Schaeffer and Stott. The aim of this paper is to present a brief overview of the Judeo-Christian Scriptures and how they have been interpreted by Christian theologians linked to strand reformed in the light of an ecological reading. An epistemological cut was made recognizing these theologians and their heterogeneous ideological positions in order to preserve the re(read) of the biblical texts chosen under the ecological perspective. White Jr. (1967), American historian, wrote an article that blamed Christianity for the environmental crisis. This speech has been confronted over the past several decades by the Christian spectrum and the theologians chosen for dialogue in this article advocate contrary positions to what was stated by White Jr., at the time. The path to the dialogue between these theologians was sought from the idea that speech is a social construction (Foucault, 2009). From the analysis of the dialogue established between the theologians and their chosen re(readings) biblical texts is possible to conclude that this new theology has the role of awareness in response to environmental crisis within the evangelical churches.